**k**(**k**+1)(2k+1)/6 must be divisible by 100 means**k**(**k**+1)(2k+1) divisible by 600 which is 5x5x2x2x2x3 2k+1 is odd, and only one of**k**or**k**+1 can be even so you need**k**or**k**+1 divisible by 8 one of**k**,**k**+1, and 2k+1 will always be divisible...4 Answers · Science & Mathematics · 18/12/2013

(

**k**-1)x^2+2x-(**k**-3)=0 suppose**k**-1=a and**k**-3=b so,a-b=**k**-1-**k**+3=2 so the equation becomes ax^2+(a-b)x-b=0 => ax^2+ax-bx-b=0 =>ax(x+1)-b(x+1)=0 =>(ax-b)(x-1)=0 x=-1 or x=b/a=(**k**-3)/(**k**-1)5 Answers · Science & Mathematics · 31/01/2011

**k**= rate/(mol/L)^3 If the rate is in mole/sec, then**k**= L^3/(mole.sec)4 Answers · Science & Mathematics · 17/05/2011

**k**-8/7+**k**= -1/5 okay :P afraid? maths <3 awesome :P love XD 5(**k**-8) = -1 (7+**k**) 5k - 40 = -7 -**k**5k+**k**= -7 + 40 6k = 33**k**= 33/62 Answers · Education & Reference · 07/10/2012

Let

**k**≥ 2. Then p_(**k**- 1) + 3**k**- 2 = (**k**- 1)[3(**k**- 1) - 1]/2 + (6**k**- 4)/2 = [(**k**- 1)(3**k**- 3 - 1) + 6**k**- 4]/2 = [(**k**- 1)(3**k**- 4) + 6**k**- 4]/2 = (3**k**² - 7**k**...1 Answers · Science & Mathematics · 13/09/2009

...1 ... equation 1 (given) - x + y +

**k**z =**k**... equation 3 (given) ——————————<ADD...2 Answers · Education & Reference · 24/04/2013

**k**-4/9=3 you want to isolate**k**to find the answer, so you have to do the operations in reverse. so**k**-4=3x9**k**-4=27**k**=27+4**k**=313 Answers · Education & Reference · 28/02/2010

Let (x -

**k**) / (x - 1) = y x -**k**= yx - y x = yx - y +**k**x - yx = y +**k**x(1 - y) = y +**k**x = (-y +**k**) / (1 - y) x = (y -**k**) / (y - 1) It would seem that the function is generally its own inverse...2 Answers · Science & Mathematics · 12/08/2010

Depends which Special

**K**you mean....... if your enquiry is in regards to cereal then the...14 Answers · Entertainment & Music · 11/01/2008

**k**(x) = 2 sin (x+π) / (sin (x+π) - 3) = 2 (- sin x) / (- sin x - 3) = 2 sin x / (sin x + 3) = [2 (sin x + 3) - 6] / (sin x + 3) = 2 - 6 / (sin x + 3) So for**k**^-1(x) we get x = 2 - 6 / (sin**k**^-1(x) + 3) => 6 / (sin**k**^-1(x) + 3) = 2 - x =>...1 Answers · Science & Mathematics · 16/12/2013